تبني التخطیط التسویقي الاستراتیجي كأداة لتفعیل قطاع السیاحة في الجزائر - مجاهدي فاتح; زدیوي عبد الرحیم (Finance and Business Economies Review, 2017)
Algeria now is forced to diversify its economy and leave the dependence on hydrocarbons, by re-launching sectors not well exploited such as tourism where natural and ecological resources are available and diverse. The valorisation of the Algerian tourist product passes through a short, medium and long-term marketing strategy that will allow attracting and retaining the local and foreign tourist customers. For this, the objective of this study is to approach the concepts of strategic marketing planning in tourism and its effectiveness in the development of the Algerian tourism product and the development of this sector in Algeria. This study concludes that despite the country's enormous natural and ecological capacities, but the lack of a long and clear marketing strategy prevents the valorization of the Algerian tourist product and the distinction of the elements of attraction in Algerian tourism.